Folios in Context: Collecting Shakespeare at the University of London. (10th March 2018) - Attar, Karen
Abstract: Shakespearean holdings at Senate House Library, University of London, shot into international prominence when in 2013 the then library director, Christopher Pressler, attempted to sell a set of the first four Shakespeare folios given to the University as part of a named special collection, to be kept together in perpetuity. By this time Shakespeare had long been described as a particular strength of the University Library, largely on the basis of its eleven seventeenth-century Shakespeare folios. Yet the Library had begun with negligible literary holdings. When it opened as the University of London Library in 1877, it did so merely with the nine-volume Cambridge edition of 1863–66, a volume of Shakespeare's poetry, and two translations of Hamlet . The current article discusses the background of those Folios, in particular the First Folio formerly owned by Sir Edwin Durning-Lawrence (noted in literature from 1821 onwards) and the set of Shakespeare folios from the library of Sir Louis Sterling. It looks at their earlier provenance and use in detail not provided by the censuses of First Folios, and explores their context within the collections of the Baconian Durning-Lawrence and the high-spot collector Sterling. The article further suggests the background which could have made an institution with no literary pretensions want the works of England's prominent playwright as means of enhancing national significance. It discusses the Library's treatment and appreciation of the Durning-Lawrence and Sterling collections and traces their influence on further acquisitions, especially under the guiding hand of University Librarian John Henry Pyle Pafford. And it shows the relationship between educational value and prestige in wanting to own antiquarian works pertaining to Shakespeare—the latter an element which no surrogate, printed or digital, can replace.